Social Skills and Postural Disorders of Young People Living with Nomophobia: The Invisible Face of Digital Addiction - Çopuroğlu, Özge Baykan; Ergün, Betül; Abakay, Hanife (Selcuk University, 2026)
Aim: This study aimed to examine the relationships between nomophobia, social skills, posture, and musculoskeletal discomfort in university students, and to explore the effects of gender and smartphone usage duration on these factors. Materials and Methods: A cross-sectional study was conducted with 138 students (94 females, 44 males) selected through simple random sampling. Nomophobia levels, social skills, postural alignment, and musculoskeletal discomfort were assessed using the Nomophobia Questionnaire (NMP-Q), Social Skills Inventory, New York Posture Rating Chart, and Cornell Musculoskeletal Discomfort Questionnaire. Results: Higher nomophobia levels were negatively correlated with social skills (r = –0.27, p < 0.01) and posture scores (r = –0.33, p < 0.01), while positively correlated with musculoskeletal discomfort (r = 0.40, p < 0.01). Regression analyses showed that nomophobia significantly predicted neck (? = 0.33, p < 0.001), upper back (? = 0.36, p < 0.001), and lower back pain (? = 0.39, p < 0.001). Female students reported higher nomophobia levels than males (p = 0.002). Participants using smartphones more than five hours daily had lower posture scores and greater musculoskeletal complaints compared to those using less than three hours (p < 0.001). Conclusions: Nomophobia is associated with poorer social skills, postural misalignment, and increased musculoskeletal discomfort. Gender and smartphone usage duration further influence these outcomes. Awareness programs promoting conscious technology use and ergonomic posture habits may help mitigate the adverse psychosocial and physical effects of digital dependency. © 2026, Selcuk University. All rights reserved.
Nomofobi ile Yaşayan Gençlerin Sosyal Becerileri ve Duruş Bozuklukları: Dijital Bağımlılığın Görünmeyen Yüzü
Keywords: Musculoskeletal disorders; nomophobia; posture; smartphone use; social skills